Measuring Sharia Bank Performance by Syari'ate Value Added Approach: Sharia Enter-prise Implementation in Sharia Banking in Indonesia - Sri Wahyuni; Pujiharto Pujiharto (Universitas Hayam Wuruk Perbanas, 2017)
This study aims to measure the financial performance of Islamic banking in Indonesia using Shari’ate Value Added Approach. This research also analyzes whether there are significant differences of financial performance of Islamic banking using the income statement approach and shari’ate value added approach. The sample of this study is islamic banking, with research period 2010-2015, selected using a purposive sampling. Financial performance used in this study is Return on Asset (ROA), Return on Equity (ROE), Net Profit to Productive Asset (NPPA), and Net Profit Margin (NPM). They were analyzed using independent sample t test. The result shows that financial performance of Islamic banking is healty. There are significant differences of financial performance (ROA, ROE, and NPM) of islamic banking measured by means of income statement approach and syari’ate value added statement approach. Yet, there is no significant difference of NPPA of Islamic banking measured by the income statement approach and syari’ate value added statement approach. The result of this study provide a significant contribution to developing syariah enterprise theory. For manager of Islamic banking, Bank Indonesia and Sharia Financial Standard Board, they can use this ese findings to make policies related to the measurement of Islamic Banking performance.